IMPLEMENTATION OF MAQASHID SHARIA PRINCIPLES IN THE WORK CULTURE OF EMPLOYEES AT BANK MUAMALAT BENGKULU BRANCH - Tri Chamauliddah; Gustiya Sunarti; Fatimah Yunus (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2025)
Previous studies on Islamic Financial Institution have primarily focused on sharia compliance in products and financial performance, while limited attention has been given to how maqashid sharia principles are embodied within employees’ work culture. This study fills that gap by analyzing the implementation of maqashid sharia values in the work culture of employees at Bank Muamalat Bengkulu Branch using a descriptive qualitative approach through interviews with leaders and staff. Thematic analysis was conducted based on the five dimensions of maqashid sharia: hifz ad-dīn (protection of religion), hifz an-nafs (protection of life), hifz al-aql (protection of intellect), hifz an-nasl (protection of lineage), and hifz al-mal (protection of wealth). The results indicate that Islamic values are internalized through the “Muamalat IDEAL” work culture (Islamic, Modern, Professional). Leaders play an active role in instilling honesty, trustworthiness, and responsibility through exemplary conduct and spiritual activities. Employees’ work practices reflect a balance between spiritual and professional aspects: integrity and honest service (hifz ad-dīn), harmonious teamwork (hifz an-nafs), continuous competency development (hifz al-aql), employee welfare (hifz an-nasl), and sharia-compliant fund management (hifz al-mal). Supporting factors include strong organizational commitment and corporate values, while the main challenges are the influence of value globalization and limited Islamic literacy among staff. Overall, the application of maqashid sharia strengthens Islamic work culture and professionalism within Bank Muamalat Bengkulu Branch.